THE RELATIONSHIP BETWEEN NURSES' KNOWLEDGE AND ATTITUDES WITH THE CONTROL OF HEALTH CARE ASSOCIATED INFECTIONS (HAIs) IN THE SURGICAL INPATIENT ROOM OF YULIDDIN AWAY HOSPITAL TAPAKTUAN - Susanti Susanti; Sri Gustini; Rasima Rasima; Cut Rahmi; Syam Irwan (Sean Institute, 2022)
Healthcare-Associated Infections (HAIs) are infections that occur in patients during treatment in hospitals and other healthcare facilities where when admitted there is no infection and not in the incubation period, including infections in hospitals but appear after the patient is discharged, these infections are also due to work on hospital workers and health workers related to the health care process in health care facilities. The study aimed to determine and analyze the relationship between nurses' knowledge and attitudes with the control of Healthcare-Associated Infections (HAIs) in the Surgical Inpatient Room of Yuliddin Away Tapaktuan Hospital. Type of quantitative research with cros-sectional study design. The population is all nurses on duty in the operating room. The number of samples was 40 nurses on duty in the surgical inpatient room of the Regional General Hospital (RSUD) dr. H. Yuliddin Away. By using the total sampling technique. The results using the Chi-square test showed that there was a relationship between knowledge and the control of HAIs in the surgical inpatient room of the Regional General Hospital (RSUD) dr. H. Yuliddin Away with a p value = 0.001 , and there was an attitude relationship with the control of HAIs in the surgical inpatient room of the Regional General Hospital (RSUD) dr. H. Yuliddin Away Tapaktuan with a pvalue = 0.001. This study recommends that the results of this study can provide input to service institutions and become guidelines in the Control of Healthcare Associated Infections (HAIs) in hospitals.